Controlling procesów logistycznych w podmiotach zależnych - Czyczerski, Marcin (Controlling of logistics processes in related companies, 2008)
The article describes the role of controlling of logistics processes in related companies. Because of globalization process logistics becomes an area which creates great challenges as well as decides about competitive advantage of companies. The increase in number of subsidiaries, resulting mostly from international expansion of corporations, provides additional challenges for the logistics processes. It gives, however, a possibility of using such solutions as collaborative forecasting. Both mentioned phenomena - increasing expectation connected with logistics as well as a still increasing number of subsidiaries cause that controlling of logistics processes in related companies is becoming more and more important. Area of interest is being shifted from assessing logistics budget and its realization toward controlling of efficiency of flow.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 56-62